KLASIFIKASI KEMAMPUAN KESUBURAN TANAH (FCC) PADA BEBERAPA SUB DAS DI DAS SEMPOR KABUPATEN KEBUMEN JAWA TENGAH - Roro Kesumaningwati; Dja’far Shiddieq; Bambang H Sunarminto (Faculty of Agriculture, Universitas Sebelas Maret, 2008)
The fertility capability soil classification system (FCC) on several sub catchment areas, Sempor catchment area of Kebumen district Central Java. Sempor catchment area have many function, one of them is as a central of agricultural sector in Sempor sub district. The agricultural sector in Sempor catchment area hasn’t been able to catch up the optimal production. The production was only sufficient to supply farmer requirement. The research in order to agricultural development uncommon to do in Sempor catchment area. The research usually talking about the sedimentation process of Sempor basin whereas for the other problems weren’t gave much attention. Sempor catchment area has different characteristic on soil physic, chemical, and fertility. The research about the fertility capability soil classification system (FCC) on several sub catchment areas, Sempor catchment area need to be done in order to agricultural development. This research was used soil survey methods, and laboratory analysis. Result of this study shown that Sempor catchment area have different in soil fertility. Sampang sub catchment area has four FCC that is LR (≥45%), LCk (15‐30%), SC (30‐45%), and LC (8‐20%). Ketegan sub catchment area has three FCC that is LCk (15‐30%), SC (30‐45%), and LC (8‐ 20%). Kedungjati sub catchment area have four FCC that is LCk (15‐30%), SC (30‐45%), C (30‐45%), and LC (8‐20%). Kalikumbang, Kaliputih, Kedungwringin, and Sempor sub catchment area have two FCC that is LCk (15‐30%), and C (30‐45%), and Seliling sub catchment area have three FCC that is LCk (15‐30%), SC (30‐45%), and C (30‐45%). Key word : catchment area, the fertility capability soil classification system (FCC)